Cardiac Structure and Function in Morbidly Obese Parturients: An Echocardiographic Study. Issue 1 (March 2020) - Buddeberg, B.S.; Fernandes, N.L.; Vorster, A.; Cupido, B.J.; Lombard, C.J.; Swanevelder, J.L.; Girard, T.; Dyer, R.A.
Abstract : ( Anesth Analg . 2019;129(2):444–449) Obesity's negative effects on cardiovascular health are well documented in the general adult population. However, little is known about the impact that obesity has on cardiovascular changes during pregnancy. The aim of this study was to compare cardiovascular health in morbidly obese pregnant women [body mass index (BMI) ≥40 kg/m 2 ] versus pregnant women of normal body mass (BMI⩽30 kg/m 2 ).